PEMBERIAN LATIHAN JALAN TANDEM LEBIH BAIK DARIPADA LATIHAN ONE LEGGED STANCE UNTUKMENINGKATKAN KESEIMBANGAN DINAMIS PADA LANSIA DI BANJAR MUNCAN DESA KAPAL KECAMATAN MENGWI KABUPATEN BADUNG - Lidia Valentin; I Nyoman Adiputra; I Putu Adiartha Griadhi; I Made Niko Winaya (Majalah Ilmiah Fisioterapi Indonesia, 2016)
ABSTRACTProblems that would arise from a balance disorder is an increased risk of falls among the elderly people. The purpose of this study was to determine giving tandem walk exercises is better than one legged stance exercise to increasing dynamic balance for elderly people.This study was an experimental study with Pre and Post Test Control Group Design. This study involved 20 subjects were divided into two groups. Data was collected by measuring the dynamic balance among the elderly people using Time Up and Go Test(TUGT)at the beginning and the end of theexercise in each group. The research showed significant result with p=0.000 in group I (tandem walk) and p=0.001 in group II(one legged stance).The test results show independent t-test p=0.000 the difference ofin dynamic balance. Based on these results it can be concluded that givingtandem walk exercises is better thanone legged stance exercise to increasing dynamic balance for elderly people. Keywords: dynamic balance, tandem walk, one legged stance, elderly people.